2020
DOI: 10.3390/ijms21217925
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-21-5p, miR-122-5p, and miR-320a-3p with 90-Day Mortality in Cardiogenic Shock

Abstract: Cardiogenic shock (CS) is a life-threatening emergency. New biomarkers are needed in order to detect patients at greater risk of adverse outcome. Our aim was to assess the characteristics of miR-21-5p, miR-122-5p, and miR-320a-3p in CS and evaluate the value of their expression levels in risk prediction. Circulating levels of miR-21-5p, miR-122-5p, and miR-320a-3p were measured from serial plasma samples of 179 patients during the first 5–10 days after detection of CS, derived from the CardShock study. Acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In other cases, various cardiomyopathies, including dilated cardiomyopathy, left ventricular ejection fraction, and ischemic cardiomyopathy, upregulated miR-21 expression levels were shown in heart tissue and circulation (53,54,58,65). In addition, increased miR-21 level was suggested as a new biomarker of cardiovascular disease-related premature death to predict patients at great risk of adverse outcomes (66,67). However, unchanged expression miR-21 level was also reported in patients with hypertrophic cardiomyopathy (53).…”
Section: Clinical Studymentioning
confidence: 99%
“…In other cases, various cardiomyopathies, including dilated cardiomyopathy, left ventricular ejection fraction, and ischemic cardiomyopathy, upregulated miR-21 expression levels were shown in heart tissue and circulation (53,54,58,65). In addition, increased miR-21 level was suggested as a new biomarker of cardiovascular disease-related premature death to predict patients at great risk of adverse outcomes (66,67). However, unchanged expression miR-21 level was also reported in patients with hypertrophic cardiomyopathy (53).…”
Section: Clinical Studymentioning
confidence: 99%
“…Among many miRNAs, the focus of this study is miR-320a-3p, a well-known miRNA, which is abnormally expressed in many cancers, such as lung cancer [17], breast cancer [18]. Previous studies have shown that miR-320a-3p levels in circulating plasma at baseline in non-survivors of cardiogenic shock are elevated and correlated with markers of hypoperfusion [19]. Second, Burns et al found in a study on adverse drug reactions that miR-320a-3p was enhanced in the serum of patients with clozapine-induced cardiotoxicity [20].…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 has been extensively studied in cancerous processes and has recently been linked to CVDs and inflammation [ 14 , 15 ]. It has been shown that circulating levels of miR-21 are increased in subjects with a higher risk of CVD death, with atherosclerosis [ 16 ], and with cardiogenic shock [ 45 ], suggesting its potential as a biomarker to assess CVD risk. Indeed, consumption of the Mediterranean diet with extra virgin olive oil seems to reduce circulating miR-21 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%